Deletion of a GC-rich region flanking the enhancer element within the long terminal repeat sequences alters the disease specificity of Moloney murine leukemia virus. - Hanecak, R (1991)
Moloney murine leukemia virus (M-MuLV) is a replication-competent retrovirus which induces T-lymphoblastic lymphoma 2 to 4 months after inoculation. Enhancer sequences in the U3 region of the M-MuLV long terminal repeat, primarily the 75-bp tandem repeats, strongly influence the disease specificity and latency of M-MuLV. We investigated the role of GC-rich sequences downstream of the tandem repeats in the disease specificity of M-MuLV. A recombinant M-MuLV lacking 23 bases of a GC-rich sequence (-174 to -151), Delta 27A M-MuLV, was tested for pathogenesis in neonatal NIH Swiss mice. Delta 27A M-MuLV induced disease with a longer latency than did M-MuLV (7 versus 3 months) in greater than 85% of inoculated mice. More interestingly, this virus showed an expanded repertoire of hematopoietic diseases. Molecular analyses and histopathologic examinations indicated that while 39% of mice inoculated with Delta 27A M-MuLV developed T-cell lymphoblastic lymphoma typical of wild-type M-MuLV, the majority developed acute myeloid leukemia, erythroleukemia, or B-cell lymphoma. Viral DNA corresponding to Delta 27A M-MuLV was detectable in most of the tumors analyzed. These findings indicate that the GC-rich region significantly influences the disease specificity and latency of M-MuLV.